The beauty complex: social media trends, effects, and opportunities - Zipporah Mwangi; Ágnes Buvár (Cogent Social Sciences, 2024)
Media plays a crucial role in the portrayal of ideal beauty standards. Research has shown that social media’s influence on conveying body ideals is greater today than that of broadcast media. Online interactions with beauty content can contribute to the appreciation of one’s internal and external features. However, these interactions can also lead to sexual objectification, appearance comparisons, and body image concerns. This study sought to investigate the emerging themes of beauty studies on social media and the potential areas of study that require scholarly attention. A systematic literature review was conducted to identify studies on beauty in social media published between January 2015 and May 2023 in two databases: Scopus and Web of Science. A thematic analysis of 32 articles established the following emerging themes: body positivity, negative effects of social media, activism, makeup, and advertising. Opportunities for areas that require scholarly attention include culture and religion, gender, longitudinal studies and experiments, the need for more representative samples, and the study of diverse social media platforms. The limitation of this study is that this subject area is still growing, and articles that had not been published at the time of data collection were not included in the current study.